Estudantes com deficiência e vulnerabilidade social: uma revisão da produção acadêmica brasileira (2015 - 2025) - Padovan, Nicole Rodrigues (Universidade Federal de São Carlos, 2025)
This Final Course Project aimed to examine how Brazilian education for students with disabilities and social vulnerability enrolled in basic education occurs. From a critical and reflective perspective, the study seeks to understand how social vulnerability intensifies educational exclusion processes and how teacher training can contribute to the implementation of truly inclusive pedagogical practices. The work was developed through bibliographic and qualitative research, based on scientific articles, legislation, and official documents published between 2015 and 2025. Productions addressing the National Policy on Special Education from the Perspective of Inclusive Education, the role of public schools, and the performance of teachers in the face of structural and social inequalities permeating the Brazilian educational context were analyzed. The results showed that, although Brazil has a solid framework focused on inclusion, there is still a significant gap between what is stipulated in legislation and the reality experienced in schools. The research indicates that the lack of ongoing teacher training, the absence of adequate infrastructure, the scarcity of pedagogical resources, and the fragility of intersectoral policies are factors that compromise the effectiveness of inclusion. Furthermore, the analysis shows that neoliberalism and capitalist logic contribute to the maintenance of educational inequalities, since quality education remains a privilege of the most favored social classes.
Students with disabilities and social vulnerability: a review of brazilian academic production (2015 - 2025)
Keywords: Educação especial; Educação básica; Vulnerabilidade social; Estudante com deficiência; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL; 4. Educação de Qualidade